Graft and viral outcomes in retransplantation for hepatitis C virus recurrence and HCV primary liver transplantation: a case–control study. (12th June 2014) - Martí, Josep; De la Serna, Sofia; Crespo, Gonzalo; Forns, Xavier; Ferrer, Joana; Fondevila, Constantino; Navasa, Miquel; Fuster, Josep; García‐Valdecasas, Juan Carlos
Abstract Introduction The use of liver retransplantation (ReLT) for hepatitis C virus (HCV) recurrence is controversial because of subsequent viral recurrence after ReLT. Methods Case–control analysis between patients undergoing ReLT for HCV reinfection between 1993 and 2012 (ReLT group: 26 patients) and patients undergoing liver transplantation (LT) for HCV infection immediately before and after each ReLT (LT group: 52 patients). Results ReLT group had worse hepatocellular function, higher preoperative viral load, higher transfusion requirements, and increased number of postoperative complications than LT group. ReLT patients showed a trend toward worse graft survival compared with LT (five‐yr graft survival: 42.3% vs. 64.3%, p = 0.145), but the rate of severe HCV recurrence and infection‐free survival (IFS) was similar. The use of donors older than 60 yr led to a lower IFS and graft survival in both groups. Early severe HCV infection rate was similar in both groups, but it affected prognosis in ReLT more markedly than in LT (three‐yr graft survival: 0% vs. 66.7%, p = 0.003). Conclusions ReLT for HCV reinfection has acceptable results when strict selection policies of donor and recipient are applied. However, early severe recurrence more markedly impairs prognosis in ReLT patients than in LT.